Copper-based catalyst with packaging structure as well as preparation method and application of copper-based catalyst
The copper-based catalyst with encapsulated structure was formed by hydrothermal treatment, and the problems of long induction period and insufficient thermal stability in the catalytic reaction of existing copper-based catalysts were solved, and the catalytic effect of high cyclohexanone selectivity and short induction period were achieved.
Patent Information
- Application Number
- CN202311046144.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-18
- Publication Date
- 2025-02-21
AI Technical Summary
The existing copper-based catalysts have obvious problems of induction period and insufficient thermal stability in catalytic reactions, and the particle size of copper species varies greatly, which affects the catalytic performance.
By mixing a mixture of silica, copper carbonate and/or copper oxide with a tetrapropyl ammonium hydroxide solution, hydrothermal treatment is performed to form a copper-based catalyst with an encapsulated structure, thereby improving the uniformity and bonding strength of the copper nanoparticles.
The copper-based catalyst has high cyclohexanone selectivity and short induction period in the cyclohexanol dehydrogenation reaction, and the preparation method is simple, and it is suitable for industrial large-scale post-treatment.
Smart Images

Figure CN119488918A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of catalyst preparation, and specifically relates to a copper-based catalyst with an encapsulation structure, in particular a copper-based cyclohexanol dehydrogenation catalyst and a preparation method and application thereof. Background Art
[0002] Compared with precious metals such as gold, silver or platinum, the price of copper is relatively low, and copper-based catalysts have shown high performance in many hydrogenation and dehydrogenation catalytic reactions, so copper-based catalysts are widely used in many industrial catalytic reactions. However, at present, copper-based catalysts still have many shortcomings: the production of copper-based catalysts is mainly carried out by precipitation method. The particle size of copper species in the catalyst prepared by this method varies greatly. This reason causes copper-based catalysts to show a significant induction period in catalytic reactions, and the thermal stability needs to be improved.
[0003] Patent CN104437488B discloses a method for preparing a catalyst for gas-phase dehydrogenation of cyclohexanol to cyclohexanone. The catalyst is mainly composed of Cu / SiO2. The catalyst is prepared by a step-by-step precipitation method. The precipitant and silica sol are precipitated, and then copper nitrate solution is added for precipitation. The catalyst is washed, solid-liquid separated, dried, roasted, and finally pressed into tablets.
[0004] Patent CN113856708A discloses a copper-based catalyst for catalytic oxidation of hydrogen chloride to produce chlorine and a preparation method thereof. The method comprises dissolving copper chloride and rare earth chloride in water, adding pseudo-boehmite and stirring evenly, then dropping potassium hydroxide solution to form a precipitate, washing, shaping, drying, and roasting at 400-550°C in an oxygen-containing atmosphere for 3-8 hours.
[0005] Patent CN113070069A discloses a cyclohexanol dehydrogenation catalyst, a preparation method and an application thereof, wherein the active components are CuO, SiO2 and Cr2O3, the structural additive is La2O3 or CeO2, the mass content of the active component CuO is 30-45%, the mass content of the active component SiO2 is 10-20%, the mass content of the active component Cr2O3 is 10-20%, and the mass content of the structural additive is 2-6%.
[0006] Li Shiwen (Chem. Commun., 2014, 50, 1824) et al. reported a method for preparing a noble metal catalyst. The method first impregnates Pt(NO3)2(NH3)4 onto a pure silicon molecular sieve silicalite-1 (S-1) carrier and then calcines it. Then, they treat 1 g of the above-obtained catalyst with 7.5 mL of a 0.55 mol / L tetrapropylammonium hydroxide solution, and after calcination and reduction, the Pt@S-1 catalyst encapsulated with Pt nanoparticles is obtained. The Pt@S-1 catalyst has a catalytic activity similar to that of the Pt / SiO2 catalyst in the toluene hydrogenation reaction, but Pt@S-1 does not show catalytic activity in the trimethylbenzene hydrogenation reaction.
[0007] Chen Yong (Chemical Engineering Journal, 2021, 419, 129641) et al. reported a method for treating S-1 molecular sieve. The method used 0.3 mol / L tetrapropylammonium hydroxide solution, with a solid-liquid ratio of 1:10, to treat S-1 at 170°C for 2 and 24 hours. Summary of the invention
[0008] The purpose of the present invention is to solve the above technical problems and provide a copper-based catalyst and a preparation method and application thereof. A high-performance copper-based catalyst is prepared by the preparation method of the present invention for catalysis of hydrogenation and dehydrogenation of organic matter. Furthermore, the preparation method of the present invention can effectively enhance the bonding strength between the active copper species and silica through a simple hydrothermal treatment, encapsulate copper nanoparticles in a carrier, and improve the uniformity of the copper nanoparticles in the catalyst, thereby preparing a catalyst with higher catalytic selectivity for the target product.
[0009] In order to solve the above technical problems, the first aspect of the present invention provides a method for preparing a copper-based catalyst with an encapsulation structure, comprising mixing a mixture of silicon dioxide, copper carbonate and / or copper oxide with a tetrapropylammonium hydroxide solution, placing the obtained solid-liquid mixture in a closed container, and then heating, filtering, drying and calcining the mixture to obtain a copper-based catalyst with an encapsulation structure.
[0010] According to some embodiments of the present invention, the raw material of the silicon dioxide uses white carbon black with a high specific surface area. Preferably, the specific surface area of the white carbon black is 145 to 300 m 2 / g, preferably 200 m 2 / g. The use of white carbon black with a high specific surface area helps to fully mix the various components of the catalyst using a simple grinding method and improve the interaction between the various components.
[0011] According to some embodiments of the present invention, the mixture of silicon dioxide, copper carbonate and / or copper oxide can be prepared by mechanical mixing without adding water, or by grinding and mixing under the condition of adding water. Based on the fact that the usual calcination temperature of copper-silicon catalyst is above 380°C, copper nanoparticles need to have a certain particle size. The present invention adopts a method of directly mixing silicon dioxide, copper oxide and / or copper carbonate raw materials to prepare a catalyst precursor. The preparation method of the copper-based catalyst of the present invention is simple.
[0012] According to some embodiments of the present invention, the mass percentages of the components of the mixture of silicon dioxide, copper oxide and / or copper carbonate and water are 30-96%, 4-70% and 0-50%, respectively, preferably 17.3%, 34.8% and 47.9%. The stirring temperature of the mixture is 5-100°C, and the mixing time is 5-300 minutes. Preferably, the mixing temperature is 25-40°C, and the mixing time is 60-120 minutes.
[0013] According to some embodiments of the present invention, the mixture of silica, copper carbonate and / or copper oxide can be directly purchased silica and copper oxide catalyst (mainly composed of silica and copper oxide) or filter cake (mainly composed of silica and (basic) copper carbonate). The mass percentages of silica, copper oxide and copper carbonate are 30-96%, 4-70% and 0-50%, respectively, preferably 65-80%, 20-35% and 5-10%, respectively; for example, 70%, 25% and 5%; 66%, 28% and 6%. The mass percentages of silica and copper oxide are 30-96% and 4-70%, respectively, preferably 65-80% and 20-35%, respectively, more preferably 65-70% and 30-35%, for example, 70% and 30%; 67% and 33%. The mass percentages of the silicon dioxide and copper carbonate are 43-96% and 4-57% respectively, preferably 60-65% and 35-40% respectively; for example 64% and 36%; 60% and 40% respectively.
[0014] According to some embodiments of the present invention, the concentration of the tetrapropylammonium hydroxide solution used in the treatment is 0.01-0.245 mol / L; the solid-liquid ratio of the mixture solid powder to the tetrapropylammonium hydroxide solution is 0.1-1. Preferably, the concentration of the tetrapropylammonium hydroxide solution is 0.1-0.12 mol / L, and the solid-liquid ratio is 0.1-0.5; for example, the concentration of the tetrapropylammonium hydroxide solution is 0.1 mol / L, and the solid-liquid ratio is 0.1; the concentration of the tetrapropylammonium hydroxide solution is 0.12 mol / L, and the solid-liquid ratio is 0.2.
[0015] According to some embodiments of the present invention, a modification aid is further added to the tetrapropylammonium hydroxide solution; the content of the modification aid in the tetrapropylammonium hydroxide solution is 0-0.3 mol / L; preferably 0.15-0.2 mol / L.
[0016] According to some embodiments of the present invention, the modification aid is selected from at least one of pseudo-boehmite, sodium aluminate, sodium oxide, potassium oxide, manganese nitrate and sodium tungstate.
[0017] According to some embodiments of the present invention, the modification aid is preferably pseudo-boehmite, manganese nitrate and sodium tungstate.
[0018] According to some embodiments of the present invention, the mass percentage of aluminum oxide in the pseudo-boehmite is 60-80%, preferably 65%.
[0019] According to some embodiments of the present invention, the mixture is mixed and stirred at a temperature of 5 to 100° C. for 5 to 300 minutes, more preferably at a temperature of 25 to 40° C. for 60 to 120 minutes. For example, the stirring temperature is 25° C. for 60 minutes or the stirring temperature is 40° C. for 30 minutes.
[0020] According to some embodiments of the present invention, the heat treatment temperature is 150-190°C, and the treatment time is 12-96 hours; preferably, the heat treatment temperature is 160-170°C, and the treatment time is 48-72 hours. For example, the heat treatment temperature is 170°C, and the treatment time is 48 hours.
[0021] According to some embodiments of the present invention, the drying temperature is 100-220°C, preferably 100-150°C, for example 100°C, 120°C or 150°C; the drying time is 4 hours to 48 hours, preferably 18-24 hours, for example 24 hours, 20 hours, 12 hours or 8 hours.
[0022] According to some embodiments of the present invention, the calcination temperature is 300 to 450° C., preferably 350 to 400° C., and the calcination time is 4 to 48 hours, preferably 12 to 24 hours.
[0023] According to some embodiments of the present invention, the preparation method further comprises introducing hydrogen into the obtained copper-based catalyst for reduction treatment; preferably, the temperature of the reduction treatment is 180-230°C.
[0024] A second aspect of the present invention provides a copper-based catalyst with an encapsulation structure, which is prepared by the above-mentioned preparation method.
[0025] According to some embodiments of the present invention, the copper-based catalyst includes silicon dioxide, copper oxide, graphite and additives in mass percentages of 30-96%, 4-70%, 0.5-3% and 0-3%, respectively, preferably 65-80%, 20-35%, 2% and 0.5-2%, respectively.
[0026] The third aspect of the present invention provides the use of the copper-based catalyst in organic matter hydrogenation and dehydrogenation catalytic technology, especially in the dehydrogenation of cyclohexanol.
[0027] The present invention provides a copper-based catalyst with an encapsulation structure, a preparation method thereof and an application thereof. The preparation method of the copper-based catalyst of the present invention has simple steps, does not use any precipitant in the process, and uses less water. Since the prepared catalyst has an encapsulation structure, it exhibits high cyclohexanone selectivity and a short induction period in the cyclohexanol dehydrogenation reaction compared with traditional supported catalysts. In addition, there are currently few post-treatment methods for industrial copper-silicon catalysts. The method proposed in the present invention can also be understood as a post-treatment method for a copper-silicon catalyst, and the method can not only further improve the cyclohexanone selectivity of the industrial copper-silicon catalyst. Beneficial Effects
[0028] (1) In the copper-based catalyst obtained by the present invention, copper oxide is encapsulated in a carrier and has a relatively uniform particle size. Therefore, the copper-based catalyst exhibits a high selectivity for cyclohexanone in a cyclohexanol dehydrogenation model reaction.
[0029] (2) The method for preparing the copper-based catalyst of the present invention can directly use industrially produced copper-silicon catalyst as raw material, so that not only the preparation process is simple, but also it can be used for large-scale post-processing of copper-silicon catalyst. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 TEM image of the copper-based catalyst with encapsulation structure prepared in Example 4.
[0031] Figure 2 This is the TEM photo of the copper-based catalyst of Comparative Example 17. Implementation
[0032] The present invention will be further described below in conjunction with the embodiments and drawings, but the present invention is not limited by these embodiments.
[0033] In the embodiment of the present invention: White carbon black was purchased from Hubei Huifu Nanomaterial Co., Ltd., hydrophilic fumed white carbon black HL380 and HL200, with a silicon dioxide content of ≥99.8wt.%; Light copper oxide was purchased from Wujiang Yongsheng Chemical Co., Ltd., with a content of ≥97wt.%; Industrial basic copper carbonate was purchased from Wujiang Yongsheng Chemical Co., Ltd., with a content of ≥97wt.%; Tetrapropylammonium hydroxide solution was purchased from Shandong Guohua Chemical Co., Ltd., with contents of 25 wt.% and 50 wt.%; Pseudo-boehmite was purchased from Yangzhou Zhongtianli New Materials Co., Ltd., with a content of 65wt.%; Sodium aluminate was purchased from Jinan Xinyue Chemical Co., Ltd., with a content of 99wt.%; Sodium hydroxide was purchased from Jinan Qinghai Chemical Co., Ltd., with a content of 98.5wt.%; Potassium hydroxide was purchased from Jinan Kunfeng Chemical Co., Ltd., with a content of ≥90wt.%; 50% manganese nitrate solution was purchased from Shandong New Kinetic Energy Chemical Co., Ltd.; Sodium tungstate was purchased from Baiyundu Biotechnology Co., Ltd., with a content of ≥99wt.%; The copper-silicon catalyst or its filter cake was purchased from NDH6 cyclohexanol dehydrogenation catalyst or its filter cake produced by Sinopec Nanjing Chemical Research Institute Co., Ltd., batch 2023A-1011. The composition of the catalyst is 63.8wt.% silicon dioxide, 30.6wt.% copper oxide, 2wt.% graphite, 1.6wt.% sodium oxide and 2wt.% water; the composition of the catalyst filter cake is 54.6wt.% silicon dioxide, 40.6wt.% copper oxide, 1.8wt.% sodium oxide and 3wt.% water.
[0034] Example 1 This embodiment provides a copper-based cyclohexanol dehydrogenation catalyst with an encapsulation structure, which is prepared by the following method: The preparation of the copper-based catalyst of the present invention is carried out in an open container. Specifically, 133 g of white carbon black (specific surface area 200 m 2 / g) was added to a container with a stirrer, followed by 73.3g of copper oxide, and finally 189.7g of deionized water, and the mixture was stirred for 90 minutes until the mixture became viscous and the stirring stopped. At this time, the total volume of the mixture was 396 mL. Then 412 mL (at this time, the solid-liquid ratio was 0.5) of a mixed solution of 0.2 M manganese nitrate and 0.12 M tetrapropylammonium hydroxide was added thereto, and the resulting mixture was transferred to a closed container and placed at a temperature of 170°C for 72 hours; finally, the product was dried at 120°C for 24 hours, and the resulting solid was crushed, dried, granulated with additives, calcined at 380°C for 12 hours, and finally pressed into tablets to obtain a copper-based catalyst. In the copper-based catalyst, the contents of silicon dioxide, copper oxide, graphite and manganese dioxide were 65.1wt.%, 32.3wt.%, 2wt.% and 0.6wt.%, respectively. Example 2
[0035] This embodiment provides a copper-based catalyst with an encapsulation structure, which is prepared by the following method: Example 1 was repeated, but 117 g of basic copper carbonate was used instead of 73.3 g of copper oxide in Example 1. At this time, the total volume of the mixture was 440 mL. Then 880 mL of a mixed solution of 0.2 M manganese nitrate and 0.12 M tetrapropylammonium hydroxide was added thereto. The other steps were repeated in Example 1. In the copper-based catalyst, the contents of silicon dioxide, copper oxide, graphite and manganese dioxide were 65.8 wt.%, 31.5 wt.%, 2 wt.% and 0.7 wt.%, respectively. Example 3
[0036] This embodiment provides a copper-based catalyst with an encapsulation structure, which is prepared by the following method: The preparation of the copper-based catalyst of the present invention is carried out in an open container, specifically, in a water bath at a temperature of 25° C., 416 mL of a mixed solution of 0.2 M manganese nitrate and 0.12 M tetrapropylammonium hydroxide is added to 208 g of NDH6 type copper-silicon catalyst filter cake. Other treatment conditions are the same as those in Example 1. In the copper-based catalyst, the contents of silicon dioxide, copper oxide, graphite, sodium oxide, and manganese dioxide are 65.6 wt.%, 30.4 wt.%, 1.5 wt.%, 2 wt.%, and 0.5 wt.%, respectively. Example 4
[0037] This embodiment provides a copper-based catalyst with an encapsulation structure, which is prepared by the following method: Example 3 was repeated, but 178 g of NDH6 catalyst was used instead of 208 g of NDH6 catalyst filter cake. The contents of silicon dioxide, copper oxide, graphite, sodium oxide and manganese dioxide in the copper-based catalyst were 65.0 wt.%, 31.0 wt.%, 1.5 wt.%, 2 wt.% and 0.5 wt.%, respectively.
[0038] The water-saving, energy-saving and environment-friendly copper-based catalyst prepared in Example 4 above has a TEM photo as shown in FIG. Figure 1 shown. Example 5
[0039] This embodiment provides a copper-based catalyst with an encapsulation structure, which is prepared by the following method: Example 1 was repeated, except that a mixed solution of 0.2 M pseudo-boehmite and 0.12 M tetrapropylammonium hydroxide was used instead of a mixed solution of 0.2 M manganese nitrate and 0.12 M tetrapropylammonium hydroxide. The contents of silicon dioxide, copper oxide, graphite and aluminum oxide in the copper-based catalyst were 65.1 wt.%, 32.2 wt.%, 2 wt.% and 0.7 wt.%, respectively. Example 6
[0040] This embodiment provides a copper-based catalyst with an encapsulation structure, which is prepared by the following method: Example 1 was repeated, but the mixed solution of 0.2 M manganese nitrate and 0.12 M tetrapropylammonium hydroxide was replaced by a mixed solution of 0.2 M sodium tungstate and 0.12 M tetrapropylammonium hydroxide. In the copper-based catalyst, the contents of silicon dioxide, copper oxide, graphite, sodium oxide and tungsten dioxide were 65.1 wt.%, 32.2 wt.%, 2 wt.%, 0.2 and 0.5 wt.%, respectively. Example 7
[0041] This embodiment provides a copper-based catalyst with an encapsulation structure, which is prepared by the following method: Example 1 was repeated, except that a mixed solution of 0.2 M potassium hydroxide and 0.12 M tetrapropylammonium hydroxide was used instead of a mixed solution of 0.2 M manganese nitrate and 0.12 M tetrapropylammonium hydroxide. In the copper-based catalyst, the contents of silicon dioxide, copper oxide, graphite and potassium oxide were 65.0 wt.%, 32.4 wt.%, 2 wt.% and 0.6 wt.%, respectively. Example 8
[0042] This embodiment provides a copper-based catalyst with an encapsulation structure, which is prepared by the following method: Example 1 was repeated, except that a mixed solution of 0.2 M potassium hydroxide and 0.12 M tetrapropylammonium hydroxide was used instead of a mixed solution of 0.2 M manganese nitrate and 0.12 M tetrapropylammonium hydroxide. The contents of silicon dioxide, copper oxide, graphite and sodium oxide in the copper-based catalyst were 65.3 wt.%, 32.1 wt.%, 2 wt.% and 0.6 wt.%, respectively.
[0043] Comparative Example 1 This comparative example provides a copper-based catalyst, which is prepared by the following method: Example 1 was repeated, but the mixing was performed in a water bath at 50° C. for 90 minutes. The contents of silicon dioxide, copper oxide, graphite and manganese dioxide in the copper-based catalyst were 65.1 wt.%, 32.3 wt.%, 2 wt.% and 0.6 wt.%, respectively.
[0044] Comparative Example 2 This comparative example provides a copper-based catalyst, which is prepared by the following method: Example 1 was repeated, but the mixing was carried out in a water bath at 25° C. for 360 minutes. The contents of silicon dioxide, copper oxide, graphite and manganese dioxide in the copper-based catalyst were 65.1 wt.%, 32.3 wt.%, 2 wt.% and 0.6 wt.%, respectively.
[0045] Comparative Example 3 This comparative example provides a copper-based catalyst, which is prepared by the following method: Example 1 was repeated, but 60.4 g of white carbon black (specific surface area 200 m 2 / g) was added to a container with a stirrer, and then 146.2g of copper oxide was added to replace 133g of white carbon black (specific surface area 200 m 2 / g) was added into a container with a stirrer, and then 73.3g of copper oxide was added. The contents of silicon dioxide, copper oxide, graphite and manganese dioxide in the copper-based catalyst were 28.1wt.%, 69.3wt.%, 2wt.% and 0.6wt.%, respectively.
[0046] Comparative Example 4 This comparative example provides a copper-based catalyst, which is prepared by the following method: Example 1 was repeated, but 198.3 g of white carbon black (specific surface area 200 m 2 / g) was added to a container with a stirrer, and then 8.3g of copper oxide was added to replace 133g of white carbon black (specific surface area 200 m 2 / g) was added into a container with a stirrer, and then 73.3g of copper oxide was added. The contents of silicon dioxide, copper oxide, graphite and manganese dioxide in the copper-based catalyst were 95wt.%, 2.4wt.%, 2wt.% and 0.6wt.%, respectively.
[0047] Comparative Example 5 This comparative example provides a copper-based catalyst, which is prepared by the following method: Example 1 was repeated, except that a mixed solution of 0.2 M manganese nitrate and 0.15 M tetrapropylammonium hydroxide was used instead of a mixed solution of 0.2 M manganese nitrate and 0.12 M tetrapropylammonium hydroxide. In the copper-based catalyst, the contents of silicon dioxide, copper oxide, graphite and manganese dioxide were 65.2 wt.%, 32.2 wt.%, 2 wt.% and 0.6 wt.%, respectively.
[0048] Comparative Example 6 This comparative example provides a copper-based catalyst, which is prepared by the following method: Example 1 was repeated, except that a mixed solution of 0.2 M manganese nitrate and 0.05 M tetrapropylammonium hydroxide was used instead of a mixed solution of 0.2 M manganese nitrate and 0.12 M tetrapropylammonium hydroxide. In the copper-based catalyst, the contents of silicon dioxide, copper oxide, graphite and manganese dioxide were 65.2 wt.%, 32.2 wt.%, 2 wt.% and 0.6 wt.%, respectively.
[0049] Comparative Example 7 This comparative example provides a copper-based catalyst, which is prepared by the following method: Example 1 was repeated, but 206 mL (in this case, the solid-liquid ratio was 1) of a mixed solution of 0.2 M manganese nitrate and 0.12 M tetrapropylammonium hydroxide was used. The contents of silicon dioxide, copper oxide, graphite and manganese dioxide in the copper-based catalyst were 65.0 wt.%, 32.4 wt.%, 2 wt.% and 0.6 wt.%, respectively.
[0050] Comparative Example 8 This comparative example provides a copper-based catalyst, which is prepared by the following method: Example 1 was repeated, but 0.2 M tetrapropylammonium hydroxide solution was used instead of the mixed solution of 0.2 M manganese nitrate and 0.12 M tetrapropylammonium hydroxide. The contents of silicon dioxide, copper oxide, graphite and manganese dioxide in the copper-based catalyst were 65.1 wt.%, 32.3 wt.%, 2 wt.% and 0.6 wt.%, respectively.
[0051] Comparative Example 9 This comparative example provides a copper-based catalyst, which is prepared by the following method: Example 1 was repeated, except that a mixed solution of 0.4 M manganese nitrate and 0.12 M tetrapropylammonium hydroxide was used instead of a mixed solution of 0.2 M manganese nitrate and 0.12 M tetrapropylammonium hydroxide. In the copper-based catalyst, the contents of silicon dioxide, copper oxide, graphite and manganese dioxide were 65.1 wt.%, 32.3 wt.%, 2 wt.% and 0.6 wt.%, respectively.
[0052] Comparative Example 10 This comparative example provides a copper-based catalyst, which is prepared by the following method: Example 1 was repeated, but the treatment was performed at 140° C. for 72 hours instead of 170° C. for 72 hours. The contents of silicon dioxide, copper oxide, graphite and manganese dioxide in the copper-based catalyst were 65.1 wt.%, 32.3 wt.%, 2 wt.% and 0.6 wt.%, respectively.
[0053] Comparative Example 11 This comparative example provides a copper-based catalyst, which is prepared by the following method: Example 1 was repeated, but the treatment was performed at 180° C. for 72 hours instead of 170° C. for 72 hours. The contents of silicon dioxide, copper oxide, graphite and manganese dioxide in the copper-based catalyst were 65.1 wt.%, 32.3 wt.%, 2 wt.% and 0.6 wt.%, respectively.
[0054] Comparative Example 12 This comparative example provides a copper-based catalyst, which is prepared by the following method: Example 1 was repeated, but the treatment was performed at 170° C. for 75 hours instead of 170° C. for 72 hours. The contents of silicon dioxide, copper oxide, graphite and manganese dioxide in the copper-based catalyst were 65.1 wt.%, 32.3 wt.%, 2 wt.% and 0.6 wt.%, respectively.
[0055] Comparative Example 13 This comparative example provides a copper-based catalyst, which is prepared by the following method: Example 1 was repeated, but the treatment was performed at 180° C. for 40 hours instead of 170° C. for 72 hours. The contents of silicon dioxide, copper oxide, graphite and manganese dioxide in the copper-based catalyst were 65.1 wt.%, 32.3 wt.%, 2 wt.% and 0.6 wt.%, respectively.
[0056] Comparative Example 14 This comparative example provides a copper-based catalyst, which is prepared by the following method: Example 1 was repeated, but calcination at 460°C for 12 hours was used instead of calcination at 380°C for 12 hours. The contents of silicon dioxide, copper oxide, graphite and manganese dioxide in the copper-based catalyst were 65.1 wt.%, 32.3 wt.%, 2 wt.% and 0.6 wt.%, respectively.
[0057] Comparative Example 15 This comparative example provides a copper-based catalyst, which is prepared by the following method: Example 1 was repeated, but calcination at 340°C for 12 hours was used instead of calcination at 380°C for 12 hours. The contents of silicon dioxide, copper oxide, graphite and manganese dioxide in the copper-based catalyst were 65.1 wt.%, 32.3 wt.%, 2 wt.% and 0.6 wt.%, respectively.
[0058] Comparative Example 16 This comparative example provides a copper-based catalyst, which is prepared by the following method: Take 1000ml of 1.0M copper nitrate solution a, co-precipitate sodium carbonate solution and 637g of silica sol JN-25 in a precipitation tank with stirring, control the precipitation temperature at 60℃~70℃, and the precipitation end point pH value is 7.5, then age at 70℃~75℃ for 30min, then add solution a to the above precipitation, wash, dry, crush, calcine at 320℃, add 13.0g of sodium carbonate, appropriate amount of water and graphite, and finally press into tablets to obtain a usable catalyst. The copper content of the copper-based catalyst is 27.9wt.%.
[0059] The above comparative example 16 refers to Example 5 in the invention patent CN104511277A.
[0060] Comparative Example 17 This comparative example provides a copper-based catalyst, which is prepared by the following method: Without post-treatment, NDH6 was placed in a reaction tube for reduction and then tested for catalytic activity.
[0061] The TEM image of the NDH6 copper-based catalyst is as follows: Figure 1 shown.
[0062] Experimental example In order to further illustrate the progress of the present invention, the copper-based catalyst samples with encapsulation structure prepared in Examples 1 to 8 of the present invention and the copper-based catalyst samples prepared in Comparative Examples 1 to 3 were subjected to reduction treatment using a mixture of hydrogen and nitrogen before dehydrogenation reaction, wherein the temperature of the reduction treatment was 180 to 230°C, the time was 180 hours, and the volume concentration of hydrogen in the mixture was 80%. The activity was evaluated in a fixed bed reactor with a specification of ¢32×2mm, specifically under the conditions of a raw material cyclohexanol space velocity of 0.60h-1, a controlled reaction temperature of 230°C, and a catalyst loading of 50ml. The results are shown in the following table .
[0063] It can be seen from the experimental results in Table 1 above that the copper-based catalysts prepared by the preparation methods of Examples 1 to 8 of the present invention have higher cyclohexanol conversion and cyclohexanone selectivity during activity evaluation even in a shorter reaction time; at the same time, it can be seen from the catalytic performance of the copper-based catalysts prepared by Examples 3-4 of the present invention that the present invention is suitable for post-treatment of industrial catalysts and further modulates the performance of the catalyst. It can be seen from Examples 1, 5 to 8 and Comparative Example 8 that the performance of the catalyst obtained by treating the catalyst with an appropriate amount of pseudo-boehmite as an auxiliary agent is higher than that of other auxiliary agents (sodium aluminate, sodium hydroxide, potassium hydroxide, manganese nitrate and sodium tungstate). Finally, the selected treatment conditions are within the optimal range proposed by the present invention, and the effect is better.
[0064] It should be noted that the embodiments described above are only used to explain the present invention and do not constitute any limitation to the present invention. The present invention has been described with reference to typical embodiments, but it should be understood that the words used therein are descriptive and explanatory words, rather than restrictive words. The present invention may be modified as specified within the scope of the claims of the present invention, and the present invention may be revised without departing from the scope and spirit of the present invention. Although the present invention described therein relates to specific methods, materials and embodiments, it does not mean that the present invention is limited to the specific examples disclosed therein, on the contrary, the present invention can be extended to all other methods and applications with the same functions.
Claims
1. A method for preparing a copper-based catalyst with an encapsulation structure, characterized in that: The preparation method comprises mixing a mixture of silicon dioxide, copper carbonate and / or copper oxide with a tetrapropylammonium hydroxide solution, placing the obtained solid-liquid mixture in a closed container, then heating, filtering, drying and calcining the mixture, adding an auxiliary agent for granulation, and finally pressing into tablets to obtain a copper-based catalyst with an encapsulated structure.
2. The preparation method according to claim 1, characterized in that: The silicon dioxide is white carbon black, and the specific surface area of white carbon black is 145-300 m 2 / g, preferably 200 m 2 / g.
3. The preparation method according to claim 1, characterized in that: Water can be added during the mixing process of silicon dioxide, copper carbonate and / or copper oxide; the mass percentages of silicon dioxide, copper oxide and / or copper carbonate and water are 30-96%, 4-70% and 0-50%, preferably 65-80%, 20-35% and 5-10%, and more preferably 34.8%, 17.3% and 47.9%, respectively.
4. The preparation method according to claim 1 or 3, characterized in that: The mixing and stirring temperature of the silicon dioxide, copper oxide and / or copper carbonate, and / or water is 5-100° C., and the mixing time is 5-300 minutes. Preferably, the mixing temperature is 25-40° C., and the mixing time is 60-120 minutes.
5. The preparation method according to claim 1, 3 or 4, characterized in that: The mixture of silicon dioxide, copper carbonate and / or copper oxide is obtained by directly grinding the raw materials with an appropriate amount of deionized water, drying and roasting, or a commercial catalyst whose main components are silicon dioxide and copper oxide, or a filter cake whose main components are silicon dioxide and copper carbonate, preferably, a filter cake or a roasted commercial product thereof; And / or, the mass percentages of silicon dioxide, copper oxide and copper carbonate are 30-96%, 4-70% and 0-50%, respectively, preferably 65-80%, 20-35% and 5-10%, respectively; And / or, the mass percentages of silicon dioxide and copper oxide are 30-96% and 4-70% respectively, preferably 65-80% and 20-35% respectively, more preferably 65-70% and 30-35% respectively; And / or, the mass percentages of the silicon dioxide and copper carbonate are 43-96% and 4-57%, respectively, preferably 60-65% and 35-40%, respectively.
6. The preparation method according to claim 1, characterized in that The concentration of the tetrapropylammonium hydroxide solution used is 0.01-0.245 mol / L; the solid-liquid ratio of the mixed solid powder to the tetrapropylammonium hydroxide solution is 0.1-1; Preferably, the concentration of the tetrapropylammonium hydroxide solution is 0.1-0.12 mol / L, and the solid-liquid ratio is 0.1-0.
5.
7. The preparation method according to claim 1 or 6, characterized in that: A modification aid is also added to the tetrapropylammonium hydroxide solution used; And / or, the content of the modification aid in the tetrapropylammonium hydroxide solution is 0-0.3 mol / L; preferably 0.15-0.2 mol / L; And / or, the modification aid is selected from at least one of pseudo-boehmite, sodium aluminate, sodium hydroxide, potassium hydroxide, manganese nitrate and sodium tungstate, preferably pseudo-boehmite, manganese nitrate and sodium tungstate; preferably, the mass percentage of aluminum oxide in the pseudo-boehmite is 60-80%, preferably 65%.
8. The preparation method according to claim 1, characterized in that: The heat treatment temperature is 150-190°C, and the treatment time is 12-96 hours; preferably, the heat treatment temperature is 160-170°C, and the treatment time is 48-72 hours; And / or, the drying temperature is 100 to 250° C., preferably 100 to 150° C., and the drying time is 4 to 48 hours, preferably 18 to 24 hours; And / or, the calcination temperature is 300-450° C., preferably 350-400° C., and the calcination time is 4-48 hours, preferably 12-24 hours; And / or, the preparation method further comprises introducing hydrogen into the obtained copper-based catalyst for reduction treatment; preferably, the temperature of the reduction treatment is 180-230°C.
9. A copper-based catalyst with an encapsulation structure, prepared by the preparation method as described in any one of claims 1 to 8, wherein the copper-based catalyst comprises silicon dioxide, copper oxide, graphite and an additive, and the mass percentages of silicon dioxide, copper oxide, graphite and the additive are 4-70%, 30-96%, 0.5-3% and 0-3%, respectively, preferably 65-80%, 20-35%, 2% and 0.5-2%, respectively.
10. The copper-based catalyst according to claim 9, characterized in that It is used for hydrogenation and dehydrogenation of organic matter, preferably for dehydrogenation of cyclohexanol.
Citation Information
Patent Citations
A method for preparing a catalyst for the gas-phase dehydrogenation of cyclohexanol to cyclohexanone
CN104437488B
Catalyst for preparing cyclohexanone from cyclohexanol through gas-phase dehydrogenization and preparation method thereof
CN104511277A
Catalyst for preparing cyclohexanone through cyclohexanol dehydrogenation, preparation method and application thereof
CN113070069A
Copper-based catalyst for preparing chlorine gas through catalytic oxidation of hydrogen chloride and preparation method thereof
CN113856708A
High-selective catalyst for dehydrogenating cyclohexanol to produce cyclohexanone and preparation method thereof
CN106890641A